Pembuatan Sistem Informasi Administrasi Pada Toko Mulia Sport - Apriko Winston Gaghana; Djoni Haryadi Setiabudi (Jurnal Infra, 2015)
Toko Mulia Sport is a shop specialized in the sale of sport tool. Toko Mulia Sport bussines prosses is still done manually. The invoice and data inventory are written by hand. The purpose of this thesis is to produce a administration information system that can help Toko Mulia Sport administrative activities.This information system is used to store items data. Purchase and sale transactions process help to assist the sale product to the customer and the purchase product to the supplier. Product item and transaction reports help to facilitate owner in looking at the data. This information system is built using Microsoft Visual Studio 2010 programming language. The  data storage system uses Microsoft SQL Server 2008.Based on test results, a system that has been created can help Toko Mulia Sport in conducting transactions or print the report.